Performance evaluation of a SARS-CoV-2 and influenza A/B combo rapid antigen test - Rosenblatt, Kevin P.; Romeu, Hugo; Romeu, Camille; Granger, Elder (Frontiers in Molecular Biosciences, 2024)
The global COVID-19 pandemic and seasonal influenza outbreaks have emphasized the critical need for accurate and efficient diagnostic tools. In this study, we comprehensively evaluated the performance of the InstaView COVID-19/Flu Ag Combo Test, designed to simultaneously detect SARS-CoV-2, influenza A, and influenza B viruses. The InstaView COVID-19/Flu Ag Combo Test exhibited robust detection capabilities, accurately identifying SARS-CoV-2, Influenza A, and Influenza B viruses over a wide concentration range (1.41X10 3 to 7.05X10 4 TCID50/mL).Extensive testing against potential cross-reactants and interferences yielded no false-positive results, indicating the high specificity of the test. Clinical evaluation further confirmed the kit's reliability, with sensitivity ranging from 95.1% to 98.2% for SARS-CoV-2, 88.9% to 95.2% for influenza A, and 91.7% to 100% for influenza B, depending on the sample type. Specificity was consistently 100% for all targeted viruses. The InstaView COVID-19/Flu Ag Combo Test thus demonstrated high performance, ease of use, rapid results, and the ability to precisely detect SARS-CoV-2 and influenza A/B infections, making it an effective tool in streamlining diagnostic workflows, optimizing resource allocation, and improving patient outcomes.